The Influence Of Rock N' Roll Culture On The Koes Brothers' Song "Poor Clown" (Roland Barthes Semiotics Study) - Septyan Fauzan; Halomoan Harahap (Journal of Social Research, 2024)
The song is titled “Poor Clown " which is the work of the phenomenal Band in Indonesia Koes Bersaudara. This song became the first rock n ' roll song that excited the old order. This song made them forced to be put in prison in the Glodok area of West Jakarta. This happened because the Indonesian government at that time strongly condemned everything that smelled Westernized because it was considered capable of eroding the culture and noble values of the nation. The purpose of this study was to find out how much influence rock n’ roll was in the song titled “Poor Clown” through the theory of semiotics from Roland Bathes. The method used is qualitative research with qualitative interpretative approach. This research uses constructivist paradigm. This study belongs to the class of subjective-constructivism because this research is based on the views and thoughts of the author personally.. The results of this study is true, the song titled “Poor Clown” by the Koes brothers became a satire for the president in the era of the Old Order, Sukarno, which was studied through the semiotics theory of Roland Barthes.